Longmire. The complete fifth season - Boyd, David, (Filmmaker); Scott, T. J. (Timothy James); Taylor, Robert, 1963-; Sackhoff, Katee; Phillips, Lou Diamond, 1962-; Johnson, Craig, 1961- (Burbank, CA : Warner Bros. Entertainment, 2017)
A sheriff struggles to turn his life around in the wake of his wife's recent passing.
A fog that won't lift -- One good memory -- Chrysalis -- The Judas wolf -- Pure Peckinpah -- Objection -- From this day forward -- Stand your ground -- Continual soiree -- The stuff dreams are made of.
Based on the mystery novel series of the same title by Craig Johnson.
Dolby digital 5.1, wide screen 1.77:1.
Robert Taylor, Katee Sackhoff, Lou Diamond Phillips, Cassidy Freeman, Adam Batley.
Originally broadcast on television in 2016.
TV rating: Not rated.
In English or Portuguese.
Keywords: Johnson, Craig, -- 1961- -- Television adaptations; Longmire, Walt (Fictitious character) -- Drama; Murder -- Investigation -- Drama; Sheriffs -- Drama; Widowers -- Drama; Detective and mystery television programs; Action and adventure television programs; Television series; Fiction television programs; Video recordings for people with visual disabilities; Crime television programs; Based on the book; Western television programs; Detective television programs; Mystery television programs